NATIONAL AND GLOBAL COMPETITIVENESS UNIVERSITY - Arrarte Mera, Raúl Alberto (2011)
Three situation news that spread in social media in a period of 45 days led to our concern to discuss said issue: Creation of the Administrative Restructuring, Organic and Functional UNMSM Commission, countersigned through Vice-Chancellor Resolution No. 03377-R-11. The installation and start-up set was due on August 5, 2011, at the Council Chamber, Jorge Basadre Building. Publication of “QS World University Rankings 2011/2012” which was based on surveys to academics and employers, which evaluates the reputation of each College, based on ongoing research. 10 first positions were granted to British and American Universities. Nationalist Congress Group “Gana Peru” Bill which proposes a new University Act. Our main objective is to provide comparative information and reflect on first world Universities in comparison to their best positioned Latin America counterparts, which provides information to our authorities who seek ways to improve our Alma Mater competitiveness to face possible future institutional changes at Peruvian State University.